2017
DOI: 10.1002/2017gl074021
|View full text |Cite
|
Sign up to set email alerts
|

The influence of sulfur on the electrical resistivity of hcp iron: Implications for the core conductivity of Mars and Earth

Abstract: Cosmochemical and geochemical studies suggest sulfur (S) as a light alloying element in the iron‐rich cores of telluric planets, but there is no report of sulfur's alloying effect on the electrical and thermal transport properties of iron (Fe); a subject that is closely related to the dynamo action and thermal evolution of planetary cores. We measured the electrical resistivity of hexagonal‐closed‐packed (hcp) structured Fe alloy containing 3 wt. % silicon (Si) and 3 wt. % S up to 110 GPa at 300 K. Combined wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
61
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(71 citation statements)
references
References 50 publications
8
61
2
Order By: Relevance
“…Indeed, seismic data indicate that the core is well mixed (Davies et al, ; Labrosse, ; Nimmo, ). However, compositional convection is still not fully resolved as there is significant uncertainty in terms of light element composition in the core (Morard et al, ; Mori et al, ; Ozawa et al, ; Shibazaki & Kono, ; Suehiro et al, ; Suer et al, ; Tateno et al, ). For example, it was recently proposed that the exsolution of Mg at the CMB is sufficient to drive compositional convection (O'Rourke et al, ; O'Rourke & Stevenson, ) from the top down.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, seismic data indicate that the core is well mixed (Davies et al, ; Labrosse, ; Nimmo, ). However, compositional convection is still not fully resolved as there is significant uncertainty in terms of light element composition in the core (Morard et al, ; Mori et al, ; Ozawa et al, ; Shibazaki & Kono, ; Suehiro et al, ; Suer et al, ; Tateno et al, ). For example, it was recently proposed that the exsolution of Mg at the CMB is sufficient to drive compositional convection (O'Rourke et al, ; O'Rourke & Stevenson, ) from the top down.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of light elements, such as S, C, and O, is expected to be in the liquid OC in relatively small quantities of a few percent (e.g., McDonough, ; Morard et al, ; Tateno et al, ; Zhang, Sekine, et al, ). It was established recently (e.g., Zhang, Sekine, et al, ) that the OC is unlikely to contain just a single light element, since it has been demonstrated that no one light element can satisfy the combined compositional, cosmochemical, and geophysical constraints in the OC near ICB (Morard et al, ; Mori et al, ; Ozawa et al, ; Shibazaki & Kono, ; Suehiro et al, ; Suer et al, ; Tateno et al, ). Even with the unknown compositional makeup of the light elements in the core, our study leads to the conclusion that the electrical resistivity and thermal conductivity of liquid Fe alloy will remain the same at ICB and likely at CMB, regardless of the light element identity for small contents.…”
Section: Discussionmentioning
confidence: 99%
“…The Lorenz number is believed to be variable with the temperatures and pressures and well discussed through theoretical calculations (de Koker et al, 2012;Pozzo et al, 2013) and experimental studies on the Seebeck coefficient of iron (Secco, 2017). However, to be comparative with previous studies (Gomi et al, 2013(Gomi et al, , 2016Gomi & Hirose, 2015;Ohta et al, 2016;Pommier, 2018;Seagle et al, 2013;Suehiro et al, 2017;Zhang et al, 2018), we use the ideal value here to calculate the thermal conductivity of Fe-P system.…”
Section: Implication For the Thermal Conductivity Of Lunar Corementioning
confidence: 99%
“…Electrical resistivity measurements on solid Fe, Fe‐Ni, and Fe‐Si alloys at high‐pressure and room temperature environment revealed that different types and content of alloy elements have different magnitude influence on the resistivity of Fe‐L alloys (L, light elements; Gomi et al, , ; Gomi & Hirose, ; Seagle et al, ). Recently, Suehiro et al () suggested that sulfur has a weaker influence than silicon by measuring the electrical resistivity of Fe‐S‐Si alloy (3 wt% S and 3 wt% Si) at pressures up to 110 GPa at 300 K. Zhang et al () reported the electrical resistivity of Fe 99 C 1 alloy (1 at.% C) and iron carbides (Fe 3 C, Fe 7 C 3 ) at pressures up to 80 GPa and at 300 K, demonstrating that carbon has a stronger effect than Si, S, and Ni in reducing the electrical and thermal conductivity of the Earth's core. Despite the studies on solid phase, high‐temperature and high‐pressure experiments (Pommier, ; Silber et al, ) and first principles calculations (Wagle et al, ; Wagle & Steinle‐Neumann, ) are all used for the resistivity of liquid Fe and liquid Fe‐S system also provides precious constraints on the thermal conductivity of liquid cores.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the cosmochemical, geochemical, and geophysical evidence, several elements, including H, C, S, O, and Si, have been suggested to alloy with iron in the core (Li & Fei, ; Poirier, ). Previous studies employing electrical resistivity measurements have investigated the pressure‐temperature effect (Ohta et al, ) and impurity resistivity of nickel (Gomi & Hirose, ), silicon (Gomi et al, , ; Seagle et al, ), and sulfur (Suehiro et al, ). These experiments reveal the significance of the thermal and light element effects that are capable of significantly altering the high‐pressure thermal conductivity of iron alloys.…”
Section: Introductionmentioning
confidence: 99%